2008
DOI: 10.1124/dmd.107.019737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spice Constituents on P-Glycoprotein-Mediated Transport and CYP3A4-Mediated Metabolism in Vitro

Abstract: ABSTRACT:The effects of eight components from six commonly consumed spices on P-glycoprotein (P-gp) transport and CYP3A4 metabolism were evaluated in vitro. P-gp-mediated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 33 publications
3
71
1
2
Order By: Relevance
“…It has been reported that activity of CYP3A4 enzyme is particularly sensitive to dietary effects [57]. Although the potential effect of food on sunitinib pharmacokinetics was not supported by the phase I study in healthy subjects, in which no difference of sunitinib and SU12662 pharmacokinetics was found between patients with single dose of sunitinib after either 10-hour fast or a high-fat meal, the effect of long-term cooking habit, such as the frequently used CYP3A4-inhibiting spices [58], could not be ignored.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that activity of CYP3A4 enzyme is particularly sensitive to dietary effects [57]. Although the potential effect of food on sunitinib pharmacokinetics was not supported by the phase I study in healthy subjects, in which no difference of sunitinib and SU12662 pharmacokinetics was found between patients with single dose of sunitinib after either 10-hour fast or a high-fat meal, the effect of long-term cooking habit, such as the frequently used CYP3A4-inhibiting spices [58], could not be ignored.…”
Section: Discussionmentioning
confidence: 92%
“…[14][15][16][17] Apparently, the differential effect of PXT on MDZ metabolism is only able to be explaind using an atypical kinetics model. A hypothesis declared that CYP3A enzyme contains two or more MDZ-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances have demonstrated that CYP3A4 cooperativity involves the binding of multiple (at least 2) substrate molecules to the binding pocket and represents a case of true allostery characterized by effector-induced conformational transitions (Davydov and Halpert, 2008). On the basis of the above theory and our results, the differential effects of PXT on the metabolism of MDZ, similar to the effectors of citral, 6-gingerol, and D-limonene (Zhang and Lim, 2008), can be explained by a two-site model (Korzekwa et al, 1998;Domanski et al, 2001) or a multi-site model (Kenworthy et al, 2001;Manoj et al, 2010;Smirnov et al, 2011) of CYP3A4. It can be hypothesized that PXT can bind to one defined site that is also occupied by MDZ in the position required for 4-hydroxylation (or 19-hydroxylation) and that both substrates can displace each other.…”
Section: Discussionmentioning
confidence: 78%
“…Drug interactions involving substrates, inhibitors, activators, or inducers of CYP3A4 are more prevalent and complex than those of other members of the P450 family (Kim et al, 2006;Pal and Mitra, 2006). It is becoming evident that many CYP3A4-mediated reactions proceed with atypical MichaelisMenten kinetics, including substrate activation (Shou et al, 1999), substrate inhibition (Lin et al, 2001;Wu, 2011), and differential kinetics Zhang and Lim, 2008;Xia et al, 2009). These phenomena are thought to be due to the binding of multiple substrates within the active site of the enzyme (Kenworthy et al, 2001;Galetin et al, 2003;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%